Soil Moisture Characteristics of Three Soils of Different Textural Classes - Jha, M. N.; Rathore, R. K. (Indian Forester, 1980)
The soil moisture characteristics of the three soils of different textural classes have been determined. The moisture contents at field capacity and the wilting point increased with increase in fineness of texture. The available moisture capacity of these soils were 4.29% in sandy loam, 18.97% in silty loam and 14.34% in clay. The silty loam soil maintained a good air-water balance. Favourable for good plant growth than observed under clay. Higher aeration pores induced better infiltration in sandy loam though found to be droughty.